Antimicrobial effects of Lepidium sativum mucilage (LS) on some pathogenic bacteria (pour plate method). - Fatemehe Majdi (19825877) (2024)
Antimicrobial effects of Lepidium sativum mucilage (LS) on some pathogenic bacteria (pour plate method).